Experimental investigation on the influences of varying injection timing on the performance of a B20 JOME biodiesel fueled diesel engine / S. Jaichandar and K. Annamalai - S., Jaichandar; K., Annamalai (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This experimental study aims to optimize the injection timing to achieve higher performance from biodiesel fueled Direct Injection (DI) diesel engine. Experiments were performed using a naturally-aspirated single cylinder DI diesel engine equipped with a conventional jerk type injection system to study the effects of varying injection timing on the combustion, performance and exhaust emissions using a blend of 20% Jatropha Oil Methyl Ester (JOME) by volume with diesel. The test results showed that improvement in terms of brake thermal efficiency and specific fuel consumption for the engine operated at retarded injection timing, particularly at 21o bTDC. Substantial improvements in reduction of emission levels particularly oxides of nitrogen (NOx) were observed for retarded injection timing of 21o bTDC. Compared to the engine operated at standard injection timing of 23o bTDC, the retarded injection timing of 21o bTDC provided a better performance of 2.27% and 3.4% in terms of BTE and BSFC respectively and NOx emission level improvement of 4.5%. However, CO, UBHC and smoke emission levels were slightly deteriorated compared to standard injection timing operation. It has also been found that retarding the injection timing lowers marginally ignition delay, peak in-cylinder pressure and maximum heat release rate.